Monitoring stanu środowiska jako element oceny realizacji polityki ekologicznej państwa - Sej-Kolasa, Małgorzata (The monitoring of environmental condition as an element of evaluation of the execution of the state's environmental policy, 2006)
The execution of the environmental policy is subject to evaluation process. The evaluation provides also indirectly informations on conditions of the environment. The monitoring serves as a tool for achieving both purposes. The aim of the article is the indication of basic assignments in the range of the monitoring of environmental policy and the access to the information on conditions of the environmen
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 168-178